Implementasi Model Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Kelas IV Mata Pelajaran Fikih di MI Mazraatul Ulum 02 Paciran - Heni Nur Rohim (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The implementation of learning in elementary school aims to develop the basic abilities of learners in the form of academic ability, life skills, moral development, strong character formation, the ability to cooperate, and aesthetic development of the surrounding world. More specifically, the abilities developed in learners at the level of basic education are logic, ethics, aesthetics, and kinetics. For students, elementary school will be more meaningful if what is learned is related to his life experience, because the child views an object in his environment as a whole. Based on the context of the above research, researchers formulate several main problems that include How the activities of teachers and learners in the implementation of the discovery learning model in Fiqh learning at MI Mazraatul Ulum 02 Paciran, and How the learning outcomes of learners in Fiqh subjects at MI Mazraatul Ulum 02 Paciran after using the discovery learning model. The type of research conducted is Classroom Action Research. The results of this study are (1) the activities of teachers in managing the learning of the material fiqh of puberty signs and their consequences in the implementation of worship in cycle I with a value of 75% with a good category, in cycle II obtained a score of 93.75% very well. And student activity in cycle I with a score of 67.18% with sufficient category, in cycle II obtained a score of 93.75% with excellent category, (2) Student learning results obtained after the application of discovery learning model in the subject of fiqh material signs of puberty and its consequences in the implementation of worship, cycle I obtained a classical completion value of 59.09%, and in cycle II with a value of 90.90%